Pengembangan Kualitas Pendidikan di Sekolah Menengah Pertama Satu Atap Negeri 3 Nainggolan Kabupaten Samosir berbasis Inovasi Strengths, Weaknesses, Opportunities, and Threats (SWOT) - Pardomuan Manullang; Saktina M. Simanullang; Mega Melati Munte; Royda Togatorop; Yohana N. Panjaitan (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
Improving the quality of education requires strategic planning that aligns institutional strengths with contextual challenges. This study examines the internal and external conditions of Sekolah Menengah Pertama Satu Atap Negeri 3 Nainggolan through a Strengths, Weaknesses, Opportunities, and Threats analysis to identify the most appropriate strategies for enhancing educational quality. The central research question focuses on how SWOT components shape strategic decision-making within the school. Using a qualitative descriptive approach, data were collected through direct observation, document analysis, and interviews with school stakeholders. The findings indicate that strengths and opportunities—such as committed educators, community support, and potential program development—serve as valuable assets in achieving institutional goals, whereas weaknesses and threats—such as limited facilities and demographic challenges—pose significant barriers to progress. The study concludes that formulating targeted, context-responsive strategies is essential to optimizing advantages while mitigating potential constraints, thereby supporting sustainable educational development.